2020
DOI: 10.1016/j.jpedsurg.2019.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Milk-Derived Extracellular Vesicles in the Protection Against Experimental Necrotizing Enterocolitis

Abstract: Purpose: Necrotizing enterocolitis (NEC) is a leading cause of death in premature infants. Breast feeding decreases the incidence of NEC but, even with aggressive promotion of nursing in Neonatal Intensive Care Units, morbidity and mortality remain high. Previous studies from our laboratory have demonstrated that extracellular vesicles (EVs) purified from mouse and rat stem cells can protect the intestines from NEC. The aim of this study was to determine whether human breast milk (BM)-derived EVs could prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 15 publications
4
65
0
Order By: Relevance
“…Using the well-characterized rat NEC model, we have demonstrated that human BM-derived EVs reduce the incidence of NEC in rat pups when delivered orally with formula feeds. Orally delivered BM-EVs had improved efficacy compared to BM-EVs delivered intraperitoneally, which may be related to the stability of the BM-EVs trafficking through the digestive tract [51,86,90]. Human BM-EVs had pro-proliferative and anti-apoptotic effects in both rat (IEC-6) and human (FHS74) intestinal cell culture models, suggesting that the therapeutic properties of BM-EVs are mediated through a protective effect on intestinal epithelial cells [86].…”
Section: Breast Milk Extracellular Vesicles and Necrotizing Enterocolmentioning
confidence: 99%
See 4 more Smart Citations
“…Using the well-characterized rat NEC model, we have demonstrated that human BM-derived EVs reduce the incidence of NEC in rat pups when delivered orally with formula feeds. Orally delivered BM-EVs had improved efficacy compared to BM-EVs delivered intraperitoneally, which may be related to the stability of the BM-EVs trafficking through the digestive tract [51,86,90]. Human BM-EVs had pro-proliferative and anti-apoptotic effects in both rat (IEC-6) and human (FHS74) intestinal cell culture models, suggesting that the therapeutic properties of BM-EVs are mediated through a protective effect on intestinal epithelial cells [86].…”
Section: Breast Milk Extracellular Vesicles and Necrotizing Enterocolmentioning
confidence: 99%
“…In the search for exosomes/EVs that have a higher propensity for therapeutic effects, while also having the potential to be easily administered clinically, BM-derived exosomes have become a key player. Recently, there has been a spike in interest of the potential beneficial effects of BM exosomes [86,87]. These effects are spread across numerous mammals, including humans, bovines, camels, and pigeons [86][87][88][89].…”
Section: Breast Milk Exosomesmentioning
confidence: 99%
See 3 more Smart Citations